EDUKASI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS WEB BAGI GURU SMK NEGERI 2 BUNGO - Yogi Irdes Putra; Arisman Sabir; Ahmad Ridoh; Fauziah Fauziah; Ana Maryana (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
The objectives of the activity to be achieved are: to increase the knowledge, understanding and skills of SMK Negeri 2 Bungo teachers in utilizing web-based learning media so that they can increase knowledge, facilitate their tasks and can increase motivation and learning outcomes of students of SMK Negeri 2 Bungo. This goal can be achieved using the model of service, namely the Model (Assistance) and the method of implementing this activity the method (Assistance), specifically the method, namely: (1). Training in the form of presenting training materials on the history of the Internet, the use of web-based learning media. This activity was accompanied by the entire implementation team (2). Assignment to make all web-based teaching materials in accordance with the expertise program of each subject teacher. Based on the results of observations during the activity, it can be seen that the participant's activity is very good, this can be seen from the many indicators of training activities that appear. Likewise with the results of the questionnaire given to participants at the end of the activity, 93% of participants were satisfied with this activity. The implementation of educational activities has been able to achieve the expected goals, this can be seen from the tasks given to participants that can be completed properly. It is hoped that the participants will use the results of the training to develop learning media in accordance with the field of study taught at school